What Is the Relevance of the Tip-Apex Distance as a Predictor of Lag Screw Cut-Out? - Goffin, Jérôme M. (Public Library of Science, 2013)
Using a simple mathematical formulation, the relationship between the position of the lag screw tip (relevant to both intramedullary and extramedullary devices) and the concept of tip-apex distance (TAD) was derived. TAD is widely used in operating theaters as a surgical guideline in relation to the fixation of trochanteric fractures, and in clinical studies as a predictor of lag screw cut-out. In order to visualize better this concept, the locus of points having the same TAD was plotted and the dependence of TAD on the location of the lag screw tip was also reported. It was shown that TAD should be adjusted for the size of the femoral head (a variable which varies a lot according to the sex of the patient) while no correlation was found between TAD and bone morphometry indices obtained from micro-CT data (BV/TV and Tb.Th). Therefore, these results seem to suggest that TAD lacks mechanical justification and that predictors which are based on mechanical properties, such as bone density, should be investigated further.